IMPLEMENTASI KEBIJAKAN PERAN PEREMPUAN DALAM PROSES PEMBANGUNAN DI KABUPATEN NDUGA PROVINSI PAPUA - Juliana Gwijangge; Vince Tebay (JURNAL KEBIJAKAN PUBLIK, 2022)
The research objectives are first to explore and examine the implementation of the Women's Empowerment Policy in the development process in Nduga Regency; second Identify the factors that hinder the role of Papuan women in the development process in Nduga Regency. Methods of data collection using questionnaires and interviews. Meanwhile, the data analysis used was qualitative descriptive method which included data reduction, data presentation and conclusion drawing. The results of the study show that firstly, policies related to women's empowerment in the development process in Nduga Regency have not been implemented optimally; The two factors that hinder the participation of Papuan women in the development process in Nduga Regency are external factors (social culture/patriarchy and local government commitment), as well as internal factors (education and dual roles). Suggestions that can be given Do partnerships with traditional leaders, communities. Youth and Women in every village, to share perceptions about increasing women's participation in every line of development; Second,Local governments can ratify various regulations originating from abroad and domestically, so that acceleration/affirmation can be created for women's empowerment in all development sectors. Third, Establish cooperation between the Office of Women's Empowerment with Universities and the Community to conduct studies that are considered for the preparation of gender-responsive regulations, programs and budgets.